2009
DOI: 10.1074/jbc.m109.064428
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by Glutathionylation of Isocitrate Lyase from Chlamydomonas reinhardtii

Abstract: Post-translational modification of protein cysteine residues is emerging as an important regulatory and signaling mechanism. We have identified numerous putative targets of redox regulation in the unicellular green alga Chlamydomonas reinhardtii. One enzyme, isocitrate lyase (ICL), was identified both as a putative thioredoxin target and as an S-thiolated protein in vivo. ICL is a key enzyme of the glyoxylate cycle that allows growth on acetate as a sole source of carbon. The aim of the present study was to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…1C). It has been reported that Chlamydomonas reinhardtii regulates isocitrate lyase by glutathionylation (51) and that a transaminase (PA0132), which was highly up-regulated in PQtreated WT cells (supplemental Table S5), can transform glyoxylate to glycine, a component of glutathione. Further experiments are warranted to investigate the role of glyoxylate in the regulation and production of glutathione in P. aeruginosa (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1C). It has been reported that Chlamydomonas reinhardtii regulates isocitrate lyase by glutathionylation (51) and that a transaminase (PA0132), which was highly up-regulated in PQtreated WT cells (supplemental Table S5), can transform glyoxylate to glycine, a component of glutathione. Further experiments are warranted to investigate the role of glyoxylate in the regulation and production of glutathione in P. aeruginosa (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy with these data, the presently described MerA-Grx1 interaction led us to speculate that MerA might be glutathionylated upon Hg 2ϩ reduction and subsequently deglutathionylated by Grx1. Hence, using standard in vitro procedures to assay glutathionylation (27,28), MerA was incubated with biotinylated glutathione (BioGSSG). Subsequently, the presence of glutathione adducts on MerA was analyzed by Western blotting using an antibiotin antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The water-soluble biotinylation reagent EZ Link Sulfo-NHS-Biotin (Perbio Science) was used to couple biotin to the primary amino group of GSSG, as described previously (28). The biotinylation reagent (40 l; 48 mM) was incubated with GSSG (40 l; 32 mM) in 50 mM potassium phosphate buffer (pH 7.2) for 1 h at room temperature, generating biotinylated GSSG (BioGSSG).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins specifically produced in n-hexane grown cells but not in succinate grown cells were an isocytrate lyase (spots B and C), a malate dehydrogenase (6D) and the subunit beta of a succinyl CoA synthetase (6D). The two different pI of isocytrate lyase are most likely caused by post-translation modifications of the protein [360]. The over-expression of the isocytrate lyase and malate dehydrogenase would suggest the key role of glyoxylate cycle in n-hexane-grown BCP1 cells as it was described in A. borkumensis, since the isocytrate lyase is the central enzyme of the cycle and malate dehydrogense has a role in restoring the isocitrate used in the cycle.…”
Section: Tca Cycle and Glyoxylate Bypassmentioning
confidence: 91%